A review of recent development for the CFD-DEM investigations of non-spherical particles - Ma, Huaqing; Zhou, Lianyong; Liu, Zihan; Chen, Mengyao; Xia, Xiuhao; Zhao, Yongzhi (Powder technology, 2022)
The coupling between fluid and granular materials is commonly encountered in nature and engineering practice. Moreover, the shape of granular materials in practical applications is normally non-spherical. Therefore, investigating the particle-fluid systems containing non-spherical particles for a deeper understanding of their underlying mechanisms and then for improving the performance of the related industrial processes should be an urgent necessity for practical needs. For investigating the intricate flow behaviors of particle-fluid systems, the numerical simulation method of coupling DEM (Discrete Element Method) with CFD (Computational Fluid Dynamics) has been widely recognized as a promising tool, and many efforts have been devoted to the CFD-DEM investigations of non-spherical particles in recent years. This paper aims to review development of the CFD-DEM investigations for non-spherical particles from theoretical models to applications in recent six years. It primarily represents three principal aspects: the theoretical foundations of DEM for modeling non-spherical particles, the coupling methodologies between CFD and DEM and the use of the non-spherical CFD-DEM coupling model in different applications involving particle-fluid flows. In the end, the conclusions and the outlooks for future investigations are given. [Display omitted]